ANALISIS PENGEMBANGAN KELEMBAGAAN FORUM CORPO-RATE SOCIAL RESPONSIBILITYDI JAWA TIMUR - Sulis Rochayatun; Puji Handayati; Gunartin . (Universitas Negeri Malang, 2016)
Abstract: Implementation of CSR program is one form of implementation of the concept of good corpo-rate governance. It is intended that the behavior of businesses have directives that can be referencedby organizing all the interests of stakeholders that can be filled proportionally, preventing significanterrors in the corporate strategy and ensures errors that occur can be corrected immediately. Basically,corporate social responsibility is expected to go back into the culture for the Indonesian nation inparticular, and the world community in unity to overcome the problem of economic, social and envi-ronmental. The population used as the sample is 10 Bappeda cities in East Java. Sampling usingpurposive sampling. The data used are primary data derived from interviews and observations. Theresults of the field studies showed that the average city does not have regulations on CSR in itsimplementation, is also no institutional model so that the CSR Forum on the results of the study datashowed that a large part of the city agencies do not have a CSR forum.Keywords:Corporate Social Responsibility ( CSR ), CSR Forum